Determinants of Brand Loyalty of Over-the-Counter Drugs - Pandey, Ashutosh; Shimona (Indian Journal of Marketing, 2024)
Purpose : This paper examined the determinants of brand loyalty for OTC drugs. It further analyzed brand experience, trust, and attachment to examine the model. Methodology : It utilized a sample of 296 users in the Delhi-NCR region in India. A quantitative research technique was used to collect the data through a questionnaire. Smart PLS was used for the quantitative analysis of the proposed model. Findings : The findings revealed that brand experience in Over-the-Counter Drugs (OTC) positively and significantly impacted brand loyalty. The findings revealed that experiential branding leads to effective brand loyalty. Practical Implication : The paper introduced the brand loyalty model for OTC brands and gave scope for developing the sustained growth of the product by working out the determinants of brand loyalty, such as brand experience, brand trust, and brand attachment. Originality : The paper proposed and validated a unique OTC brand loyalty model.